Analysis of the mediating effect on relationship between job searching activities and willingness to work of college graduates - Kim, Soo-Kyung (Edelweiss Applied Science and Technology, 2025)
This study aimed to examine the mediating effect of job failure experiences and recognizing the cause of failure in the job search process after college graduation. This study confirmed the statistical significance of the parameters through the Baron and Kenny (1986) three-step mediating effect analysis method. In Step 1, the effect of the job search activities on the job search failure experience through the mediation of their job search failure experience was examined, and the analysis results revealed the static effect of the college graduates' willingness to work (β=.133, p<.05). In Step 2, the static effect of the job search activities was confirmed on the college graduates' willingness to work (β=.086, p<.01). In Step 3, analysis results showed that the job search activities had a mediating effect by mediating the experience of job search failure and influencing the college graduates' willingness to work. Additionally, the research model was revised based on the results of analyzing the partial mediating effect of recognizing the cause of failure in the relationship between the job search failure experience and the willingness to work.